Thermophysical correlation of hybrid nanofluids (HNFs): A thematic review - Masyfu’ah, Mokhtar; Abdul Rahman, Mohd Kasim; Iskandar, Waini; Wan Nur Syahidah, Wan Yusoff; Mohammed Al-Sharifi, Hussein Ali (Semarak Ilmu Publishing, 2024)
Hybrid nanofluidsrepresentinnovative fluid class that combine the advantages of nanoparticles with base fluid to enhance the heat transfer capabilities. It exhibits higherheat transfer capabilities compared to traditional nanofluids. Researchers have seized abundant opportunity to further investigate the unknown behaviour of hybrid nanofluidsover different geometries and physical parameters numerically by implementing a certain model of correlation. However, fromthe literature, these correlation models sometimes underestimate the experimental data of thermal performance. Thus, it is crucial for this review paper to discuss these modelsfor advancing research in this field. Utilizing keyword search and filtering parameters, 354 journal articles from the Scopus and Web of Science (WoS) databases were found.Following the application of the inclusion and exclusion criteria process, only 60 papers were evaluated as final articles. These studies were further classifiedinto seventypes ofcorrelations: Devi, Modified Devi Type A, Modified Devi Type B, Modified Devi Type C, Takabi, Modified Takabiand Xue model.It is found that Xue model is widely used for solving hybrid nanofluidsflow problem which dealing with carbon nanotube particle. While Devi and Takabi-based model are extensively used for non-carbon nanotube particle. Thisstudy provides valuable insightsfor future research to further study the hybrid nanofluid flow precisely and increase the heat transfer performance.